2016
DOI: 10.1371/journal.pone.0168217
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerations and Caveats in Press Releases and Health-Related Science News

Abstract: BackgroundExaggerated or simplistic news is often blamed for adversely influencing public health. However, recent findings suggested many exaggerations were already present in university press releases, which scientists approve. Surprisingly, these exaggerations were not associated with more news coverage. Here we test whether these two controversial results also arise in press releases from prominent science and medical journals. We then investigate the influence of mitigating caveats in press releases, to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 16 publications
8
132
2
3
Order By: Relevance
“…[8][9][10][11] However, there are substantial barriers that prevent journalists from improving the scientific quality of their reports, 12 and evaluations have found major shortcomings of health stories in the media. [13][14][15][16][17][18][19][20][21][22][23] Therefore, audiences must be able to appraise the reliability of claims about treatment effects in the mass media, as elsewhere. This includes claims about the effects of drugs, surgery and other types of "modern medicine"; claims about lifestyle changes, such as changes to what you eat or how you exercise; claims about herbal remedies and other types of "traditional" or "alternative medicine"; claims about public health and environmental interventions; and claims about changes in how healthcare is delivered, financed and governed.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] However, there are substantial barriers that prevent journalists from improving the scientific quality of their reports, 12 and evaluations have found major shortcomings of health stories in the media. [13][14][15][16][17][18][19][20][21][22][23] Therefore, audiences must be able to appraise the reliability of claims about treatment effects in the mass media, as elsewhere. This includes claims about the effects of drugs, surgery and other types of "modern medicine"; claims about lifestyle changes, such as changes to what you eat or how you exercise; claims about herbal remedies and other types of "traditional" or "alternative medicine"; claims about public health and environmental interventions; and claims about changes in how healthcare is delivered, financed and governed.…”
Section: Introductionmentioning
confidence: 99%
“…There is further bad news, but with a silver lining. A 2016 study of press releases again found that the prime source of exaggeration in news was the press release, but it found no evidence that exaggerations boosted the likelihood of news coverage, or that caveats decreased media interest . “Our studies found that if you hype a press release, it is no more likely to get into the news than if you don't”, Chambers commented.…”
Section: A Simplified Picture Of Sciencementioning
confidence: 91%
“…This is something that most people struggle to do, and it is becoming increasingly important because patients are taking on a bigger role in managing their health and 13 while needing to cope with more and more health information, much of which is not reliable. [14][15][16][17] Teaching critical thinking…”
Section: Essential Skills For Doctors and Patientsmentioning
confidence: 99%